Enhancing Mini Volleyball Forearm Passing Performance with Small-Sided Games and Drill Practice (British Journal of Multidisciplinary and Advanced Studies, 2024)
Forearm passing is a crucial aspect of volleyball, but young students often find themselves in need of guidance during their Physical Education (PE) classes. This study determined the effectiveness of small-sided games and drill practice in enhancing forearm passing skills. A quasi-experimental design was employed, utilizing complete enumeration sampling. The sample consisted of 26 learners from each group who participated in small-sided games and drill practice. The interventions were carried out over six weeks, including the pretest and post-test phases. Given the vulnerability of the participants, who were kindergartners and first graders, all necessary ethical protocols were strictly observed. The data was analyzed using descriptive statistics, t-tests for independent samples, and t-tests for paired samples. The results show that both interventions revealed increased scores in their forearm passing skills from Fair to Good levels. Moreover, both groups demonstrated comparable effectiveness in improving passing skills in mini volleyball, with no statistically significant difference between the two. These findings suggest that both interventions can enhance forearm passing skills in mini volleyball, offering flexibility in training approaches without compromising performance improvement. Furthermore, further investigation into the specific elements of small-sided games and drill practice that contribute to skill improvement in mini-volleyball could be beneficial.